Measuring post-production losses in livestock value chains - Wane, Abdrahmane; Iheanacho, Okike; Fadiga, Mohamadou; Mtimet, Nadhem; Njiru, Nelly; Staal, Stephen J.; Katjiuongua, Hikuepi (International Livestock Research Institute, 2023)
Measuring post-production losses in livestock value chains - developing a common method to measure losses to improve value chain performance.